The man who loved Levittown - Wetherell, W. D., 1948- (Pitt Drue Heinz Lit Prize Ser., 1985)
This book is characterized by narrative vitality and emotional range. & In Wetherell's stories a suburban retiree's assumptions about the ethos of Long Island life are challenged and dismissed by a younger generation, a young English woman achieves miracles by dancing with wounded soldiers during World War II, a tennis-mad bachelor plays an interior game as real to him as an actual match, and a black drifter converts an Asian couple to his bleak vision of American life and finds strange kinship with them.